2012
DOI: 10.1136/neurintsurg-2012-010265
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided cryoablation for palliation of secondary trigeminal neuralgia from head and neck malignancy

Abstract: CT-guided percutaneous cryoablation is an efficient minimally invasive method for the palliative treatment of TN secondary to recurrent invasive head and neck carcinoma as a result of direct tumoral invasion of the extracranial divisions of the trigeminal nerve. Patients meeting the therapeutic criteria of individuals treated for musculoskeletal metastatic lesions may benefit from this treatment. The results suggest it may not currently be a curative technique as one patient's symptoms returned, but it could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Percutaneous cryoablation for pain palliation has been performed in patients with neoplastic and metastatic disease in multiple organs, such as bone, kidney and prostate [2]. Cryoablation has also been used for patients with trigeminal [9] and genitofemoral neuralgia [5]. ICN cryoablation in particular has been described in randomized trials that compared surgical cryoanalgesia to narcotics during surgery or shortly after.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Percutaneous cryoablation for pain palliation has been performed in patients with neoplastic and metastatic disease in multiple organs, such as bone, kidney and prostate [2]. Cryoablation has also been used for patients with trigeminal [9] and genitofemoral neuralgia [5]. ICN cryoablation in particular has been described in randomized trials that compared surgical cryoanalgesia to narcotics during surgery or shortly after.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoanalgesia therapy has been recently performed under ultrasound [6] and CT guidance [7]. While ultrasound may rapidly detect pneumothorax [6], iceball formation is better visualized on CT and CBCT [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported experience for cryoablation of head and neck tumors is limited to few reports. 83,88 Guenette et al reported a series of nine patients, where regional ablation for pain relief or functional status preservation was achieved in eight patients, with no associated mortality or permanent neurovascular or cosmetic morbidity. 83 In the head and neck region, direct visualization of the ablation zone is of value given the densely packed vital structures.…”
Section: Cryoablationmentioning
confidence: 99%
“…While CT-guided and MRI-guided percutaneous aspiration of head and neck tumors is well documented (10,11), the literature of head and neck ablation is sparse, limited primarily to case reports, and limited primarily to CT- and US-guided radiofrequency ablation (for example 1215) with a few reported successful CT-guided cryoablation and MRI-guided laser-induced thermotherapy procedures (16,17). None of these techniques visualize the precise margins of ablation.…”
Section: Introductionmentioning
confidence: 99%